Westonci.ca is the ultimate Q&A platform, offering detailed and reliable answers from a knowledgeable community. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve [tex]\( f(x) \div g(x) \)[/tex], where [tex]\( f(x) = x^3 + 6x^2 + x^{\frac{1}{2}} \)[/tex] and [tex]\( g(x) = x^{\frac{1}{2}} \)[/tex]:
1. Write the division of the functions explicitly:
[tex]\[ \frac{f(x)}{g(x)} = \frac{x^3 + 6x^2 + x^{\frac{1}{2}}}{x^{\frac{1}{2}}} \][/tex]
2. Divide each term in the numerator by the term in the denominator:
[tex]\[ \frac{f(x)}{g(x)} = \frac{x^3}{x^{\frac{1}{2}}} + \frac{6x^2}{x^{\frac{1}{2}}} + \frac{x^{\frac{1}{2}}}{x^{\frac{1}{2}}} \][/tex]
3. Simplify each term individually:
- For the first term:
[tex]\[ \frac{x^3}{x^{\frac{1}{2}}} = x^{3 - \frac{1}{2}} = x^{\frac{6}{2} - \frac{1}{2}} = x^{\frac{5}{2}} \][/tex]
- For the second term:
[tex]\[ \frac{6x^2}{x^{\frac{1}{2}}} = 6x^{2 - \frac{1}{2}} = 6x^{\frac{4}{2} - \frac{1}{2}} = 6x^{\frac{3}{2}} \][/tex]
- For the third term:
[tex]\[ \frac{x^{\frac{1}{2}}}{x^{\frac{1}{2}}} = x^{\frac{1}{2} - \frac{1}{2}} = x^0 = 1 \][/tex]
4. Combine the simplified terms:
[tex]\[ \frac{f(x)}{g(x)} = x^{\frac{5}{2}} + 6x^{\frac{3}{2}} + 1 \][/tex]
Thus, the simplified result of [tex]\( \frac{f(x)}{g(x)} \)[/tex] is:
[tex]\[ \boxed{x^{\frac{5}{2}} + 6x^{\frac{3}{2}} + 1} \][/tex]
Therefore, the correct answer is:
C. [tex]\( x^{\frac{5}{2}} + 6x^{\frac{3}{2}} + 1 \)[/tex]
1. Write the division of the functions explicitly:
[tex]\[ \frac{f(x)}{g(x)} = \frac{x^3 + 6x^2 + x^{\frac{1}{2}}}{x^{\frac{1}{2}}} \][/tex]
2. Divide each term in the numerator by the term in the denominator:
[tex]\[ \frac{f(x)}{g(x)} = \frac{x^3}{x^{\frac{1}{2}}} + \frac{6x^2}{x^{\frac{1}{2}}} + \frac{x^{\frac{1}{2}}}{x^{\frac{1}{2}}} \][/tex]
3. Simplify each term individually:
- For the first term:
[tex]\[ \frac{x^3}{x^{\frac{1}{2}}} = x^{3 - \frac{1}{2}} = x^{\frac{6}{2} - \frac{1}{2}} = x^{\frac{5}{2}} \][/tex]
- For the second term:
[tex]\[ \frac{6x^2}{x^{\frac{1}{2}}} = 6x^{2 - \frac{1}{2}} = 6x^{\frac{4}{2} - \frac{1}{2}} = 6x^{\frac{3}{2}} \][/tex]
- For the third term:
[tex]\[ \frac{x^{\frac{1}{2}}}{x^{\frac{1}{2}}} = x^{\frac{1}{2} - \frac{1}{2}} = x^0 = 1 \][/tex]
4. Combine the simplified terms:
[tex]\[ \frac{f(x)}{g(x)} = x^{\frac{5}{2}} + 6x^{\frac{3}{2}} + 1 \][/tex]
Thus, the simplified result of [tex]\( \frac{f(x)}{g(x)} \)[/tex] is:
[tex]\[ \boxed{x^{\frac{5}{2}} + 6x^{\frac{3}{2}} + 1} \][/tex]
Therefore, the correct answer is:
C. [tex]\( x^{\frac{5}{2}} + 6x^{\frac{3}{2}} + 1 \)[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.